Enhancing Students’ Interest in Islamic Religious Education Through Information Technology-Based Learning Media: A Case Study at An Indonesian Islamic Junior High School - Miftahurohman, Miftahurohman; Fatimah, Meti (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This study aims to analyse the use of information technology-based learning media to increase interest in learning Islamic Religious Education at MTs Muhammadiyah 1 Gondangrejo. The research method used was descriptive qualitative, with data collected through observation, interviews, and documentation. The research participants consisted of one Islamic Religious Education teacher and 30 eighth-grade students, selected purposively. This study was conducted over two months, from August to September 2025. The results show that Islamic Religious Education (PAI) teachers utilise hardware such as laptops, LCD projectors, and speakers, as well as visual and audio media in the form of interactive presentations, learning videos, and Islamic films to present learning materials in an engaging and structured manner. The use of these media successfully increased student focus and attention, facilitated understanding of abstract material, and fostered student motivation and active engagement in learning. In conclusion, the use of information technology-based learning media effectively increases interest in learning Islamic Religious Education, making the learning process more lively, relevant, and meaningful for students.